Constant Strain Rate Uniaxial Compression of Green Sandstone during SHPB Tests Driven by Pendulum Hammer. (2nd November 2017) - Li, S. H.; Zhu, W. C.; Niu, L. L.; Dai, F.
Abstract : During the Split-Hopkinson pressure bar (SHPB) tests driven by pendulum hammer, employing a proper special shape striker is an effective way to obtain dynamic stress equilibrium condition and to get constant strain rate of the rock specimen. To find the proper special shape striker, a striker with a cambered surface was introduced and eight geometrically different hammers were designed to analyze the effect of hammer geometry on the waveform of excited incident stress waves. Based on experiments and simulations, parameter effects, including the cambered hammer curvature radius and hammer diameter, length, and impact velocity, on the incident wave shape were examined. These parametric studies provided guidelines for achieving constant strain rates in rock specimens during SHPB tests. The use of different diameter hammers was noted for shaping stress-time curves to follow the stress-strain behavior of green sandstone. Finally, to examine the applicability of using hammer geometry for shaping incident waves to achieve constant strain rate, SHPB tests on green sandstone specimens were conducted. The results demonstrated that a constant strain rate (100 s −1 ) lasting for 70  μ s was achieved with the 8# hammer (3.7 kg; curvature radius, diameter, and length of 100, 70, and 126.3 mm, resp.). In addition, dynamic experiments on green sandstone were carried out under various strain rates and the results showed that the initial tangential modulus was almost unaffected by strain rate. The strain at peak stress tended to increase with rising strain rate and the dynamic strength of green sandstone showed an apparent rate dependency.